2022
DOI: 10.3389/fpsyg.2022.961949
|View full text |Cite
|
Sign up to set email alerts
|

Motivation of non-monogamous adults to engage in sex with their different partners

Abstract: This study compared motivations of individuals in non-monogamous relationships to engage in sex with their different partners (n = 596, out of which 103 non-consensual non-monogamous, 135 polyamorous, 204 swinging, 154 in open relationships; women—38.8%, men—59.7%, other gender—1.5%; age range: from 18 to 65+ years; 86% of respondents between 25 and 54 years old; majority of the respondents are in a long-term relationship). The research aim was to identify whether there are differences in reasons to engage in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Procreation as a reason to engage in sex was removed from the questionnaire due to the virtual nature of work. In the context of previous studies, factor analysis indicated that each item is measuring a different dimension as each variable was loading heavily on a single factor only ( Kelberg and Martinsone, 2022 ). See Table 2 for the full list of questions.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…Procreation as a reason to engage in sex was removed from the questionnaire due to the virtual nature of work. In the context of previous studies, factor analysis indicated that each item is measuring a different dimension as each variable was loading heavily on a single factor only ( Kelberg and Martinsone, 2022 ). See Table 2 for the full list of questions.…”
Section: Methodsmentioning
confidence: 98%
“…To explore the motivation of chat hosts to engage in sex with their virtual clients and real-life partners, authors used a modified YSEX? questionnaire ( Meston and Buss, 2007 ), that was modified in the context of other studies for the purposes of non-monogamous populations ( Kelberg and Martinsone, 2021 , 2022 ) and demonstrated the questionnaire’s effectiveness in measuring the motivation of both monogamous and non-monogamous individuals. Chat hosts were asked to answer a set of 16 questions about their motivation to engage in sex with their real-life partners and the same set of questions in regards to their motivation to have sex with their virtual partners (a Likert scale from 1 to 5, where “1” was “none of my experiences” and “5” was “all of my experiences”).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigating the role of otherness in relationships in future work could also generate new insights into two additional areas of relationship science: infidelity and consensual nonmonogamy (CNM). In one study of people’s motivation for having sex with a secondary partner, in both CNM and nonconsensually nonmonogamous situations, people engaged in sex with their secondary partner more often to experience something they could not with their primary partner (e.g., fetish, different gender; Kelberga & Martinsone, 2022). Therefore, otherness may play a role in people’s motivation for nonmonogamy (Perel, 2017), whether with the consent of their primary partner or not.…”
Section: Future Directions In Understanding the Maintenance Of Desire...mentioning
confidence: 99%